Visual impairment in any eye adversely affects quality of life: Psychometric validation of the Malay NEI VFQ-25 - Jee Yao Loke; Sanjay Rampal; Jemaima Che Hamzah; Yi Wen Lim; Tengku Ain Kamalden (PLoS ONE, 2025)
Purpose To cross-culturally translate and adapt the National Eye Institute Visual Functioning Questionnaire (NEIVFQ-25) into Malay or Bahasa Malaysia, and to analyze its psychometric properties in a cohort of Malaysian patients with visual impairment from various causes. Design Cross-sectional validation study Methods The NEI-VFQ 25 was translated and cross-culturally adapted into the Malay version. Total of 324 visually impaired patients caused by cataracts, glaucoma, age-related macular degeneration (ARMD) or diabetic macular edema (DME), and a control group were included. Psychometric analysis was performed including test-retest and internal consistency reliability, convergent validity, discriminant validity, and factor analysis. Clinical validity was measured by correlation of clinical measurements with subdomain scores and known-groups comparison. Results Participants’ average age was 60.4 years (SD 15.4) and 47.2% were male. The internal consistency was high in most subdomains, with Cronbach alpha ranging from 0.66–0.89. The test-retest reliability was high (intraclass correlation coefficient 0.92). Even when just one eye had impaired vision, participants scored much lower on the Malay NEIVFQ 25, highlighting how well the questionnaire reflects the real impact of visual impairment. Moderate correlations were detected between visual acuity and the ‘General vision’, ‘Near Activities’, ‘Distance Activities’, ‘Social Functioning’, ‘Mental Health’, ‘Role Difficulties’, ‘Dependency’ and ‘Driving’ subdomains suggesting that these subdomains were associated with central vision. Factor analysis demonstrated that 4 factors can be extracted from 12 subdomains. Conclusions This study revealed that the Malay version of the NEIVFQ-25 is a valid, reliable, and reproducible instrument to measure the vision-related quality of life in patients with visual impairment. Quality of life was adversely affected even with only one eye having poor vision.